2002
DOI: 10.1007/3-540-46004-7_31
|View full text |Cite
|
Sign up to set email alerts
|

Disruption Management for an Airline — Rescheduling of Aircraft

Abstract: Abstract. The Aircraft Recovery Problem (ARP) involves decisions concerning aircraft to flight assignments in situations where unforeseen events have disrupted the existing flight schedule, e.g. bad weather causing flight delays. The aircraft recovery problem aims to recover these flight schedules through a series of reassignments of aircraft to flights, delaying of flights and cancellations of flights. This article demonstrates an effective method to solve ARP. A heuristic is implemented, which is able to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…The DAR solver developed in the Descartes project is based on an extension of the local search heuristic presented by Løve et al [28]. A heuristic approach were chosen due to the time requirements.…”
Section: The Dar Model and Solution Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The DAR solver developed in the Descartes project is based on an extension of the local search heuristic presented by Løve et al [28]. A heuristic approach were chosen due to the time requirements.…”
Section: The Dar Model and Solution Approachmentioning
confidence: 99%
“…The initial testing surprisingly showed that the SALS heuristics were superior to the ILS heuristic. A more in-depth description of the model developed and the results of the initial testing can be found in Løve et al [28].…”
Section: The Dar Model and Solution Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dedicated Aircraft Recovery module of the DESCARTES project is based on the methods described in the project. A summary of the findings can be found in [26].…”
Section: Aircraft Recoverymentioning
confidence: 99%
“…Their complexity varies according to the number of constraints addressed. Typical scheduling problems in the airport domain are: aircraft scheduling (Bian, Burke, Jain & Kendall, 2005;El Moudani & Mora-Camino, 2000;Gurtner, Bongiorno, Ducci & Miccichè, 2016;Yan & Chen, 2008), ground crew scheduling (Clausen, 2011), disruption management (Pereira, Fadigas, Senna & Moret, 2011) (Løve, Sørensen, Larsen & Clausen, 2002), aircraft landing sequence scheduling (García Ansola, García Higuera, Pastor & Otamendi, 2011;Tavakkoli-Moghaddam, Yaghoubi-Panah & Radmehr, 2012) or personnel training scheduling (Brucker, Qu & Burke, 2011). Particularly in the domain of personnel scheduling, the most popular type of scheduling problem is the aircraft crew scheduling, while the problem of ground crew has mainly been neglected.…”
Section: Introductionmentioning
confidence: 99%